Method to estimate sample size in repeated measurement analyses - Freitas, Alfredo Ribeiro de (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to evaluate a method to estimate the number of individuals (n) to be used in experiments involving multivariate analyses of repeated measurements over time on the same experimental unit. The method was tested with data from milk production taken monthly up to complete 10 controls (t = 1, 2, ... , 10) or evaluation conditions of Holstein cows. The estimates of n were obtained by a SAS program considering a t-variate normal distribution, zero mean vector, and covariance matrix Σ, Hotelling T2 statistical, F-distribution with noncentrality parameter δ2Δ. The link of the observed data with the method is made by means of the variance-covariance matrix. The method estimates the value of n required to detect significative differences (Δ) between any two means on each t > 2 evaluation condition, considering combinations of levels of type I error (α), power of the test F (1-β) and D. For the 10 evaluation conditions the n ranged from 11 to 89 and was affected mostly by variation in D, followed by a and b.